The millipede family Diplomaragnidae Attems 1907 in the Korean Peninsula, with the descriptions of a new genus and new species (Diplopoda, Chordeumatida) - Mikhaljova, Elena V.; Lim, Kil-Young (Zootaxa, 2008)
The diplopod family Diplomaragnidae Attems 1907 appears to be represented in the Korean Peninsula by five genera and ten species. One genus and three species are described here as new to science: Koreagna gen. n., with the type species Koreagna obtecta sp. n., Tokyosoma bellum sp. n., and Tokyosoma phialiferum sp. n. Keys and taxonomic and distributional notes are given for all species of diplomaragnids currently known from Korea.